Complexities of Stable Carbon and Nitrogen Isotope Biogeochemistry in Ancient Freshwater Ecosystems: Implications for the Study of Past Subsistence and Environmental Change - Guiry, Eric (Frontiers in Ecology and Evolution, 2019)
Stable carbon and nitrogen isotope analyses of human and animal tissues have become an important means of studying both anthropogenic and natural food webs in aquatic ecosystems. Within the rapidly expanding field of human and animal paleodietary analyses, archaeologists routinely incorporate isotopic data from fish, birds, and aquatic mammals into their interpretations of ancient freshwater resources use; however, these studies rarely consider the complex and dynamic nature of the carbon and nitrogen cycles that give structure to nutrient regimes and their isotopic compositions in freshwater ecosystems. This review outlines two thematic areas in which this surge in stable isotope applications to the study of ancient human societies could be enhanced by incorporating concepts from limnology, ecology, and biology. First, building on studies conducted in modern ecosystems, this paper outlines key aspects of the stable isotope ecology of freshwater environments, highlighting the importance of considering physical and biological processes associated with ancient biogeochemical cycles when conducting human paleodietary reconstructions. Second, this paper discusses areas where isotopic analyses of archaeological freshwater animal remains could contribute to broader research fields including climate change and cultural eutrophication research, human impacts on long-term food web dynamics and animal behaviour, and by providing novel approaches to reconstructing ancient fish management practices.